The Nexus Between Institutional Quality and Inflation in Emerging Markets: A Panel Causality Test with a Fourier Function - Cicen , Yildirim Beyazit (Ekonomika, 2023)
It is important to note that institutional quality has a substantial impact on a country’s long-term economic growth, which influences other economic indicators, such as inflation and monetary policy. An in-depth examination of the existence of this crucial relationship was conducted by applying a novel and robust panel Yilanci Gorus Fourier causality test between 2000 and 2019 to 24 developing countries, in order to detect this relationship. A recent inflation rate, the standard deviation of inflation, and sound money are all interconnected and mutually causally related to property rights and the quality of the legal system. Weakness in institutions can exacerbate financial shocks, thereby affecting monetary indicators, and monetary policies will deteriorate the quality of the institution as a result.